Field Expansion and Contraction: How Communities Shape Social and Symbolic Boundaries - Grodal, Stine (Administrative Science Quarterly, 2018)
To investigate how participants shape a field’s social and symbolic boundaries over time, I conducted an in-depth longitudinal study of five core and peripheral communities in the emerging nanotechnology field from the early 1980s to 2005. I show that core communities—futurists and government officials—initially expanded both social and symbolic boundaries to increase the field’s monetary and cultural resources, yet later they reversed course and contracted the field’s boundaries. I explain this shift by showing how an increase in resources enticed peripheral communities (service providers, entrepreneurs, and scientists) to claim membership in the field. Such claims created a self-reinforcing cycle—some peripheral communities enlarged the symbolic boundary of the field to grow the field, but this social and symbolic expansion threatened the identity of core communities and their ability to access resources. Core communities thus attempted to restrict the symbolic boundary and use this narrow definition to police membership claims by peripheral communities aiming to access the field’s resources. I develop a theoretical model of how debate over a field’s identity and resources shapes its social and symbolic boundaries. I show how different communities strategically manipulate field boundaries depending on their identification with the field. Core communities seek to keep the social and the symbolic boundaries aligned, while peripheral communities that identify only weakly with the field pursue their self-interested actions irrespective of whether these actions misalign the social and symbolic boundaries.